Systemic treatment in advanced melanoma: innovative perspectives - Ugurel, Selma; Schadendorf, Dirk (Onkologie, 2003)
Malignant melanoma is a tumor of increasing incidence. Patients with early diagnosed and surgically excised primary tumors have a high probability to be completely cured. In contrast, the prognosis of patients with distant organ metastases is still extremely poor despite a variety of therapeutical efforts that have been evaluated in numerous clinical trials. Cytotoxic treatment using single agents as well as polychemotherapy revealed only temporary clinical responses but no improvement of patients’ overall survival. Likewise, therapy regimens combining cytostatics with cytokines showed no substantial benefit compared to cytostatics alone. Due to these disappointing results, recent research strategies focused on the elucidation of the mechanisms responsible for the complex therapy resistance of melanoma. New treatment concepts have been developed to overcome some of these mechanisms. Another promising approach is the development of advanced vaccination strategies. This paper reviews a selection of innovative therapeutic strategies that are currently tested in clinical trials; in particular pretherapeutic chemosensitivity testing, chemosensitization by downregulation of bcl-2, vaccination with autologous peptide-pulsed dendritic cells and immunomodulation by histamine.
Gesehen am 23.11.2020